European trade credit use and SME survival - McGuinness, Gerard; Hogan, Teresa; Powell, Ronan (Journal of Corporate Finance, 2018)
We examine if trade credit helped financially constrained SMEs survive the recent financial crisis. Using data for 202,696 SMEs across 13 European countries over the period 2003–2012, we show that trade credit had a large positive impact on firm survival, such that a one standard deviation increase in trade credit results in a 21% decrease in the likelihood of distress. We also report evidence of a significant redistribution effect, with cash rich or unconstrained SMEs extending significantly more net trade credit than their less financially resourced counterparts. The results are robust to several econometric concerns.